2019
DOI: 10.1002/jbmr.3680
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Cell-Derived Juxtacrine Wnt1 Signaling Regulates Osteoblast Activity and Osteoclast Differentiation

Abstract: Human genetic evidence demonstrates that WNT1 mutations cause osteogenesis imperfecta (OI) and early‐onset osteoporosis, implicating WNT1 as a major regulator of bone metabolism. However, its main cellular source and mechanisms of action in bone remain elusive. We generated global and limb bud mesenchymal cell–targeted deletion of Wnt1 in mice. Heterozygous deletion of Wnt1 resulted in mild trabecular osteopenia due to decreased osteoblast function. Targeted deletion of Wnt1 in mesenchymal progenitors led to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 47 publications
(72 reference statements)
2
28
0
Order By: Relevance
“…Notum acts as a negative regulator of Wnt signaling pathway by specifically mediating depalmitoleoylation of Wnts (2). Wnt1 activates canonical Wnt/β-catenin signaling via LRP5/6 receptors by cell-cell physical contact and regulates osteoclastogenesis with OPG in a juxtacrine manner (11). By binding to cell surface receptors, Wnt1 activates a canonical signaling pathway that increases cellular β-catenin activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notum acts as a negative regulator of Wnt signaling pathway by specifically mediating depalmitoleoylation of Wnts (2). Wnt1 activates canonical Wnt/β-catenin signaling via LRP5/6 receptors by cell-cell physical contact and regulates osteoclastogenesis with OPG in a juxtacrine manner (11). By binding to cell surface receptors, Wnt1 activates a canonical signaling pathway that increases cellular β-catenin activity.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout mice of the homozygous Int-1 displayed a severe phenotype, ranging from death to ataxia (10). Conditional knockout of Wnt1 in mesenchymal progenitors led to severe fractures in mice resembling severe osteogenesis imperfecta (OI) (11). Overexpression of Wnt1 induces duplication of the embryonic axis (6,12).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in vitro Rac1 seems to mediate wnt signal effects [24]. Since intermittent parathyroid hormone stimulates bone formation and a major pathway for bone formation is driven by wnt signaling we hypothesized that the deletion of Rac1 in preosteoblasts will prevent the increase in bone formation in response to PTH [16,27].…”
Section: Deletion Of Rac1 In Preosteoblasts Does Not Prevent the Respmentioning
confidence: 99%
“…The canonical wnt signaling pathway has also been studied [16], Indeed, studies on the canonical wnt signaling sclerostin led to the development of a therapeutic agent directed against the inhibitor sclerostin for the treatment of osteoporosis that was recently approved for use in patients in the US [17].…”
Section: Introductionmentioning
confidence: 99%
“…(22) Meanwhile, it was reported that inactivation of Wnt1 in osteoblast lineage cells causes low bone mass with accompanying fractures, and we could additionally demonstrate that inducible Wnt1 expression in osteoblasts causes a rapid osteoanabolic response, which does not require Lrp5. (23–25)…”
Section: Introductionmentioning
confidence: 99%